AN ANALYSIS OF VISITOR PROFILES AND SATISFACTION TOWARDS JUNGLELAND ADVENTURE THEME PARK, SENTUL CITY BOGOR, INDONESIA (Journal of Event, Tourism and Hospitality Studies, 2021)
There are various components such as diverse products and services offered to the theme park visitors as an ‘all-inclusive theme park experience’. The necessities in satisfying the needs of theme park visitors are crucial in retaining and attracting visitors to the park. The absence of research in visitor perceived experience at the Indonesian theme park has led this study to examine the profiles and satisfaction level of visitors at the theme park. This study aims to examine the profiles and factors that contributed to visitor satisfaction at JungeLand Adventure Theme Park, Indonesia. A total of 384 questionnaires were distributed to previous visitors at JungeLand Adventure Theme Park using ‘Google Forms’ between August to October 2020. The questionnaire was meant to assess the demographic profiles and the factors influencing the satisfaction level of the theme park visitors. Descriptive statistical analysis was used to examine the satisfaction of visitors towards various components at the theme park. Findings revealed that single, high-school female students aged between 18 to 22 years old, are the majority of visitors to the theme park, who visits the park mostly on weekends and companied by friends. Visitors were mostly satisfied with the ‘Interaction with Staff’ variables, followed by the ‘Facilities’ for rides available at the park and the discount and promotion of ‘Ticket Prices’. Findings provide reliable suggestions for developing effective promotional materials, which in turn will help theme park operators to enhance their offerings and services while also enriching visitors’ experiences.